Kurikulum tarbiyah ruhiyah perspektif Said Hawwa - Jihad, Muhammad; Wibowo, Sigit; Widyasari (Program Studi Magister Pendidikan Islam,Sekolah Pascasarjana Universitas Ibn Khaldun Bogor, 2025)
The concept of Islamic education with its characteristics that are comprehensive, complete, balanced between mind, body, and spirit will give birth to a generation that can carry out its mandate as a servant of Allah as well as its role as a caliph to prosper the earth and bring goodness and emprovemen. However, it is found that some graduates of Islamic educational institutions do not show the performance that should be in the form of harmony between knowledge and deeds. The reason is that the aspect of ruhiyah that encourage the emergence of motivation and awareness to do has not received the proper touch in the implementation of education. This ruhiyah crisis encouraged an Islamic figure Said Hawwa to write the book Tarbiyatuna Ruhiyyah. Based on this background, this research aims to analyze tarbiyah ruhiyah Said Hawwa and rearrange it within the framework of four curriculum components including objectives, materials, methods, and evaluation. The research method used is a qualitative method with a literature study approach. The results of the study describe the nature of tarbiyah ruhiyah perspective Said Hawwa, then the urgency, principles, objectives, material, method and evaluation. The concept of tarbiyah ruhiyah which has been compiled in curriculum format is recommended to be a guide in organizing the tarbiyah ruhiyah process in Islamic educational institutions. Abstrak Konsep pendidikan Islam dengan ciri khasnya yang komprehensif, lengkap, seimbang antara akal, jasad, dan ruh akan melahirkan generasi yang bisa menjalankan amanah sebagai hamba Allah Swt sekaligus perannya sebagai khalifah yang akan memakmurkan bumi dan membawa perbaikan serta kebaikan. Namun, ditemukan fakta bahwa sebagian lulusan lembaga pendidikan Islam tidak menunjukkan performa yang seharusnya berupa keselarasan antara ilmu dan amal. Penyebabnya adalah aspek ruhiyah yang mendorong munculnya motivasi dan kesadaran untuk beramal belum mendapat sentuhan yang seharusnya dalam penyelenggaraan pendidikan. Krisis ruhiyah ini mendorong seorang tokoh Islam Said Hawwa menulis kitab Tarbiyatuna Al-Ruhiyah. Berdasarkan latar belakang tersebut, penelitian ini bertujuan untuk menganalisis tarbiyah ruhiyah Said Hawwa dan menyusunnya kembali dalam bingkai empat unsur kurikulum meliputi tujuan, materi, metode, dan evaluasi. Metode penelitian yang digunakan adalah metode kualitatif dengan pendekatan studi pustaka. Hasil penelitian memaparkan tentang hakikat tarbiyah ruhiyah perspektif Said Hawwa, kemudian urgensinya, prinsipnya, tujuannya, materinya, metodenya dan evaluasinya. Konsep tarbiyah ruhiyah yang telah disusun dalam format kurikulum direkomendasikan menjadi panduan dalam penyelenggaraan proses tarbiyah ruhiyah di lembaga pendidikan Islam.